Biomechanical analysis of the mechanical environment of the cell nucleus in serum starvation-induced vascular smooth muscle cell differentiation - Kazuaki NAGAYAMA (Journal of Biomechanical Science and Engineering, 2019)
Vascular smooth muscle cells (VSMCs) actively remodel the arterial walls through biomechanical signals and dedifferentiate from the contractile to the synthetic phenotype under pathological conditions. It is important to elucidate the mechanism underlying phenotypic transition of VSMCs for understanding their role in the pathophysiology of disease and for developing engineered tissues. Although numerous studies have reported various biochemical or biomechanical factors that stimulate the phenotypic transition of VSMCs, very little is known about the changes in the mechanical environment of intracellular nucleus that are involved in various cellular functions. This study investigated the changes in the force exerted on the intracellular nucleus, and their morphology and mechanical properties during serum starvation-induced VSMC differentiation. Fluorescent microscopy image analysis and atomic force microscopy nano-indentation live cell imaging revealed that the serum-starvation culture conditions markedly promote the contractile differentiation of VSMCs with F-actin stabilization and reduces the internal force exerted on the nucleus. The nuclei in these contractile VSMCs exhibited surface stiffening and matured nuclear lamina. Additionally, the nuclei exhibited distinct surface dimples along the actin stress fibers even though these nuclei were exposed to lower internal forces. These results indicate that the distinct dimples on the nuclear surfaces represent a plastic remodeling of the nucleus under the serum-starvation culture conditions. The nuclear stiffening, local deformation, and plastic remodeling observed in this study may be important factors in contractile differentiation of VSMCs.